Improving immunization in Afghanistan: results from a cross-sectional community-based survey to assess routine immunization coverage - Raveesha R. Mugali; Farooq Mansoor; Sardar Parwiz; Fazil Ahmad; Najibullah Safi; Ariel Higgins-Steele; Sherin Varkey (BMC, 2017)
Abstract Background Despite progress in recent years, Afghanistan is lagging behind in realizing the full potential of immunization. The country is still endemic for polio transmission and measles outbreaks continue to occur. In spite of significant reductions over the past decade, the mortality rate of children under 5 years of age continues to remain high at 91 per 1000 live births. Methods The study was a descriptive community-based cross sectional household survey. The survey aimed to estimate the levels of immunization coverage at national and province levels. Specific objectives are to: establish valid baseline information to monitor progress of the immunization program; identify reasons why children are not immunized; and make recommendations to enhance access and quality of immunization services in Afghanistan. The survey was carried out in all 34 provinces of the country, with a sample of 6125 mothers of children aged 12-23 months. Results Nationally, 51% of children participating in the survey received all doses of each antigen irrespective of the recommended date of immunization or recommended interval between doses. About 31% of children were found to be partially vaccinated. Reasons for partial vaccination included: place to vaccinate child too far (23%), not aware of the need of vaccination (17%), no faith in vaccination (16%), mother was too busy (15%), and fear of side effects (11%). Conclusion The innovative mechanism of contracting out delivery of primary health care services in Afghanistan, including immunization, to non-governmental organizations is showing some positive results in quickly increasing coverage of essential interventions, including routine immunization. Much ground still needs to be covered with proper planning and management of resources in order to improve the immunization coverage in Afghanistan and increase survival and health status of its children.